The Fusion of Competence and Integrity Problems in Transformation of Public Human Resources Management Model - Dahlan Dahlan; Fatmawada Fatmawada (Jurnal Ilmiah Ilmu Administrasi Publik, 2019)
The limited quality of human resource management in the Biak Numfor Regency in Papua requires fundamental transformation. Based on available data, the determinants that reject the transformation process include two categories, namely, lack of competence and integrity. This study uses a post-positivistic interpretive phenomenological philosophy that emphasizes the meaning and descriptive process to understand the process of transformation. Local government leaders who are not trustworthy in applying the concept of human resource management based on the Cakar thesis latently significantly affect the integrity of the domestic apparatus. That has an impact on the lack of credibility of the Biak Regional Human Resources Development Agency. In short, increasing the competency of human resources as an effort to produce adequate human resources in this region becomes an important key for successful transformation.